Pengembangan Media Rekam Layar Bandicam Tema Diriku untuk Meningkatkan Keterampilan Membaca Permulaan di Kelas I Sekolah Dasar - Khofifah, Nur; Ngatmini, Ngatmini; Purnamasari, Iin (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2023)
This research and development was motivated by the low reading skills of the first graders of SDN Sumurbanger 02 based on observations and interviews with classroom teachers. This study aims to produce bandicam screen recording media to improve early reading skills. The type of research used is ADDIE development research (analyze, design, development, implementation, and evaluation). developed by Dick and Carry. The purpose of this development research is to produce video-based learning media products from the bandicam application that are valid, practical, and effective to improve early reading skills in class I SDN Sumurbanger 02. The instruments used in data collection are media expert validation sheets, material expert validation sheets, teacher and student legibility sheets, pre-test and post-test questions. The results of the media expert validity test got an average score of 82 with an interval of X > 79.86 with a very good category. The results of the material expert validity test got an average score of 38.5 with an interval of X > 37.8 with a very good category. The results of the practicality test based on student responses got an average score of 23 with an interval of X > 21 with a very good category. The results of the practicality test based on the teacher's response got an average score of 47.7 with an interval of X > 42.06. The effectiveness of the bandicam screen recording media was tested valid based on the t-test got a sig (2-tailed) of 0.000 so that Ho was rejected, while the average N-Gain was 0.30 in the moderate increase category. It can be concluded that the bandicam screen recording media is proven to be valid and feasible to use in learning.